PENDAMPINGAN PENGEMBANGAN UMKM NIMELS KITCHEN MELALUI OPTIMALISASI STRATEGI PEMASARAN DIGITAL - Ni Komang Diah P.A.; Ketut Indra laksana.T.P.; Wynedhi Yudishtiro; Moch Bryan Ardy S.; Frisky Christian K.; Saifani Syahir S.; Muhamad Syauqy T.; Tri Siwi Agustina; Elsa Yustika Putri (Berajah Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting economic growth, particularly in the rapidly growing culinary sector. One MSME with strong development potential is Nimels Kitchen, a food and beverage business located in Surabaya that specializes in brownies, cakes, and cookies. Despite offering high-quality products and holding halal certification, Nimels Kitchen still faces several challenges, particularly in digital marketing. The business has not fully optimized social media as a promotional platform, its brand awareness remains relatively low, and its ordering system still relies on a pre-order model. This community assistance program aimed to strengthen Nimels Kitchen’s digital marketing strategy through a participatory approach involving field observations, semi-structured interviews, SWOT analysis, and the implementation of solutions tailored to the partner’s needs. The program included the development of a Linktree integrated with WhatsApp Business, the creation of a digital product catalog, product photography training, and recommendations for Instagram Reels and TikTok content strategies. The results indicate that Nimels Kitchen’s digital promotional media became more organized, product information became easier for customers to access, and the business owner gained a better understanding of the importance of digital marketing in business development. Although the impact on sales growth could not yet be measured due to the relatively short implementation period, the program successfully established a stronger digital marketing foundation that is expected to expand market reach, enhance brand awareness, and support the long-term sustainability of the business.